BIMBINGAN DAN PENYULUHAN PENTINGNYA ARSIP KELUARGA: GERAKAN MASYARAKAT SADAR ARSIP - Erlangga Andi Sukma; Izzatul Ulya; Rizka Rahmawati; Becik Gati Anjari (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2022)
Managing family archive independently is one of the ways that can be used to activate the family function and give universal values of the family. By knowing the important of family archive management, it is urgently needed to provide guidance and training for the students’ mothers of TK Dharma Wanita Sengkaling, Dau, Malang, so they can do the archive management for their own family. This service is done by applying participatory method, a method that involved the service offers to directly involved in the activity. The activity was started with first, sharing about how to archive classification, practice in implementing technology in archive storing and the last one was the discussion. From the result of this service, it can be concluded that the participants of the activity are satisfied for by the result of the activity: they have online drive that can be used to save their family archive so they can avoid any damaging risk in the future.